2011
DOI: 10.1007/s12603-011-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different strategies of referral to a fall clinic: How to achieve an optimal casemix?

Abstract: This study suggests that patients referred to a multidisciplinary fall prevention clinic by their general practitioner have a different risk profile than those selected by case finding using the CTI. These differences have consequences for the reach of secondary care for fall-preventive interventions and will probably influence the effectiveness and efficiency of a fall prevention program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The first multidisciplinary falls clinic was set up in Melbourne, Australia in 1988 2. Subsequently, the number of falls clinics has increased substantially since the late 1990s including Australia,1–4 USA,5–8 UK,9 France,10 Denmark,11 Spain,12 Hong Kong,13 Canada,14 Germany,15 and The Netherlands 16. In contrast, in Latin America the information related to falls clinics is scarce with reports only from Brazil and Colombia 17,18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first multidisciplinary falls clinic was set up in Melbourne, Australia in 1988 2. Subsequently, the number of falls clinics has increased substantially since the late 1990s including Australia,1–4 USA,5–8 UK,9 France,10 Denmark,11 Spain,12 Hong Kong,13 Canada,14 Germany,15 and The Netherlands 16. In contrast, in Latin America the information related to falls clinics is scarce with reports only from Brazil and Colombia 17,18…”
Section: Introductionmentioning
confidence: 99%
“…In those guidelines, NICE suggested that specialist falls services should be operationally linked to bone health (osteoporosis) services and recommended that an osteoporosis risk assessment should be an essential element of a comprehensive falls assessment 21. Since the release of these guidelines, the number of falls clinics that integrates a bone health component has grown exponentially, particularly at university hospitals 13,14,16. However, standardizing these programs and making them efficient in different cultures and practices is still a challenge.…”
Section: Introductionmentioning
confidence: 99%